PENGARUH JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq )BELUM MENGHASILKAN - Hairul, Izet; Syafrullah, Syafrullah; Hawayanti, Erni (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2016)
Effect of Organic Fertilizer Type on Growth Oil Palm Immature. (Elaeis guineensisJacq). This studyaims to get the kind of organic fertilizer best effect on plant growth of immature oil palm(ElaeisguineensisJacq). The research activities carried out from May to August 2014. This study used arandomized block design (RAK) Single, with 4 treatment was repeated six times, with three plants examples.As for the fertilizer dosage in this study is a dose of NPK fertilizer 4 kg / plant / year, a dose of organicfertilizer livestock manure 10 ton / ha, the dose of organic fertilizer industry waste palm oil (solid) 5 tons / ha,plus organic fertilizer dose of 750 kg / ha , The parameters observed in this study are 1. Plant height (cm),2.The length of the leaf midrib (cm), 3. Number of leaf midrib, 4. Chemical properties of the soil at thebeginning of the study, 5.Chemical properties of the soil at the end of the study. Based on the analysisresults obtained that the treatment of organic fertilizer very significant effect on plant height increment